Barriers and facilitators to condom use among People Who Inject Drugs in Georgia: A qualitative study guided by the COM-B model - Tamar Zurashvili; Maia Kajaia; Oluwabusayomi Akeju; Jack DeHovitz; Mamuka Djibuti (PLoS ONE, 2026)
People who inject drugs (PWID) are at a heightened risk of contracting and transmitting HIV due to shared needles and unsafe sexual practices. Evidence on what shapes condom use among PWID in Georgia is limited. We conducted qualitative study among PWID recruited from two harm-reduction organizations in Tbilisi and Samegrelo between June-August 2025. Interviews were guided by the COM-B framework and analyzed thematically. Reduced sexual pleasure emerged as a dominant capability-related barrier to condom use. Knowledge of risks, benefits, and where to obtain condoms supported condom use, although participants noted that some community members lacked such knowledge. Opportunity factors were mixed. The convenient access to condoms, whether purchased at pharmacies or available for free at harm-reduction centers, created opportunity for condom access, and facilitated condom use; the factors impeding the use included the cost of purchase as well as long distance to and restricted hours of outlets, and occasional stock-outs and concerns about quality of condoms at harm-reduction centers. Social dynamics emerged as essential factors. Partner pressure, coercion, and persuasion, often intensified by alcohol or drug use, limited condom negotiation, whereas partner support, preparedness, and peer information sharing facilitated condom use. Motivation-related barriers included being under the influence of alcohol or stimulants and “heat of the moment” impulsivity, alongside low perceived risk with regular partners. Motivators included a strong desire for self and partner protection, heightened risk perception with casual or commercial partners, fear of infection, and past negative experiences including infections or unintended pregnancy. Findings indicate that condom use among PWID in Georgia is shaped by interplay of capability, opportunity, and motivation factors. Culturally sensitive, locally adapted strategies addressing pleasure-related concerns through education, strengthening negotiation and refusal skills, including couple-focused approaches can improve consistent condom use in Georgia and may benefit other countries in Eastern Europe and Central Asia.